Status OHIS-S dan Kesehatan Gingiva terhadap Percaya Diri Pada Remaja - Erwin Erwin; Suhikma Sofyan; Andi Nur Asmayanti (Politeknik Kesehatan Kemenkes RI Jakarta I, 2017)
OHI-S is a state of oral and dental hygiene measured by a debris score and calculus of a person's teeth. Gingiva is part of the outer periodontal tissue. Self-confidence is a positive attitude of someone who enables him to develop a positive assessment of himself and his environment. The aim of the study was to determine the relationship of OHI-S status and gingival health to self-confidence in class VII adolescents at Unaaha 2 Public High School. Type of correlative analytic research with cross sectional approach. Data collection techniques are questionnaire and examination. The sample amounted to 103 people. Analysis techniques with the SPSS program and statistical tests using chi square. The test results of the relationship of OHI-S status to confidence with the chi square analysis test. The value of ????-value = 0.00 <Î± = 0.05 thus H0 is rejected and H1 is accepted so that there is a relationship between the status of OHI-S and self confidence in adolescents of class VII at Unaaha Public High School 2. The test results on the relationship of gingival health to self-confidence with the chi-square analysis value ????-value = 0.00 <Î± = 0.05 thus H0 is rejected and H1 is accepted so that there is a relationship between gingival health status and confidence in class VII youth at Unaaha 2 Public High School.